2018
DOI: 10.1111/cea.13302
|View full text |Cite
|
Sign up to set email alerts
|

Fixed airflow obstruction relates to eosinophil activation in asthmatics

Abstract: Background: Some asthmatics develop irreversible chronic airflow obstruction, for example, fixed airflow obstruction (fixed-AO). This is probably a consequence of airway remodelling, but neither its relation to inflammation nor which asthma biomarkers can be clinically useful are elucidated. We hypothesized that the presence of type 2 inflammation relates to fixed-AO. Objectives:To evaluate the presence of four markers for type 2 inflammation in fixed airflow obstruction among asthmatics.Methods: This was a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
6
15
0
1
Order By: Relevance
“…Our study demonstrated that increased sputum EDN levels but not sputum NE levels were associated with decreased %FEV 1 and %FVC in EA, which was not observed in the younger asthmatic patients. Our findings coincided with those of several studies, showing an association between increased urinary EDN and decreased FEV 1 in children [23,24] or decreased FEV 1 /FVC in adults [25]. In particular, the significant correlation between increased urinary EDN and decreased FEV 1 /FVC was observed in asthmatics ≥54 years old [25].…”
Section: Collaboration Of Edn and Ne On Airflow In Elderly Asthmaticssupporting
confidence: 92%
See 1 more Smart Citation
“…Our study demonstrated that increased sputum EDN levels but not sputum NE levels were associated with decreased %FEV 1 and %FVC in EA, which was not observed in the younger asthmatic patients. Our findings coincided with those of several studies, showing an association between increased urinary EDN and decreased FEV 1 in children [23,24] or decreased FEV 1 /FVC in adults [25]. In particular, the significant correlation between increased urinary EDN and decreased FEV 1 /FVC was observed in asthmatics ≥54 years old [25].…”
Section: Collaboration Of Edn and Ne On Airflow In Elderly Asthmaticssupporting
confidence: 92%
“…Our findings coincided with those of several studies, showing an association between increased urinary EDN and decreased FEV 1 in children [23,24] or decreased FEV 1 /FVC in adults [25]. In particular, the significant correlation between increased urinary EDN and decreased FEV 1 /FVC was observed in asthmatics ≥54 years old [25]. Additionally, 2 studies demonstrated that type-2 inflammation is amplified in EA [26,27].…”
Section: Collaboration Of Edn and Ne On Airflow In Elderly Asthmaticssupporting
confidence: 92%
“…Fixed airflow limitation was associated with lower lumen area, thickened walls in distal airways, higher blood neutrophilia, plus blood and bronchoalveolar eosinophilia and high circulating periostin and ADAM33. So fixed airway obstruction is associated with Th2 markers as demonstrated in earlier studies …”
supporting
confidence: 58%
“…[1] This disease is mostly caused by extensive and changeable airflow obstruction. [2] It is a clinically refractory disease characterized by severe asthma, inability to lie down, shortness of breath in the nose and chest tightness. At present, there are about 300 million asthmatic patients in the world, and about 30 million of asthmatic patients in China.…”
Section: Introductionmentioning
confidence: 99%